Extending rarity: discovery of the rare braconine genus, Carinibracon van Achterberg (Hymenoptera: Braconidae) in the Oriental region with the description of a new species from south India - Ranjith, A.p.; Manjusha, B.m.; Kumar, P. Girish; Nasser, M. (Zootaxa, 2018)
The extremely rare, monobasic Afrotropical braconine genus, Carinibracon van Achterberg, is recorded for the first time from the Oriental region through the description of a new species, C. orientalis Ranjith sp. nov. from south India. An illustrated key to the two known species is provided along with re-illustration of the type species of the genus, C. danielssoni van Achterberg.